The Streptococcus sanguinis competence regulon is not required for infective endocarditis virulence in a rabbit model. - Jill E Callahan; Cindy L Munro; Todd Kitten (PLoS ONE, 2011)
Streptococcus sanguinis is an important component of dental plaque and a leading cause of infective endocarditis. Genetic competence in S. sanguinis requires a quorum sensing system encoded by the early comCDE genes, as well as late genes controlled by the alternative sigma factor, ComX. Previous studies of Streptococcus pneumoniae and Streptococcus mutans have identified functions for the >100-gene com regulon in addition to DNA uptake, including virulence. We investigated this possibility in S. sanguinis. Strains deleted for the comCDE or comX master regulatory genes were created. Using a rabbit endocarditis model in conjunction with a variety of virulence assays, we determined that both mutants possessed infectivity equivalent to that of a virulent control strain, and that measures of disease were similar in rabbits infected with each strain. These results suggest that the com regulon is not required for S. sanguinis infective endocarditis virulence in this model. We propose that the different roles of the S. sanguinis, S. pneumoniae, and S. mutans com regulons in virulence can be understood in relation to the pathogenic mechanisms employed by each species.